Spoczynkowe oraz Powysilkowe Zmiany Stezenia kortyzolu i testosteronu u dwóch zawodniczek judo wagi ciezkiej w okresie przygotowan do waznych zawodów. Badania kazuistyczne - Obminski, Z.; Borkowski, L.; Lerczak, K.; Blach, W. (Medycyna sportowa, 2000)
Two heavy-weight female judoists were studied throughout April to July, the period of preparation for a high-rank competition. One judoist (A) has been a member of National Team for many years, achieved many successes in World and European Championships and was preparing for Olympic Games in Sydney. The other athlete (B) is considerably younger with a short training experience as a senior; she was preparing for European Championships in May. Both athletes had almost identical training programmes. Capillary blood was sampled at 0800 on consecutive days of 4 selected microcycles lasting globally 23 days. Before starting microcycles 1 and 4, the athletes were subjected to the Wingate test, taking place at noon hours. On those days blood was sampled at 0800, just before the exercise, 9 and 30 min post-exercise. Cortisol and testosterone in serum was determined with the use of commercial ELISA kits (IBL, Germany). The initial, resting concentration of cortisol was in subject A over 2,5-fold higher than in subject B but this difference greatly diminished at the end of the study period. Mean resting cortisol concentration was significantly higher in subject A than B (914 ± 178 and 658 ± 107 nmol/L, respectively; p < 0,001) while no significant differences were found between microcycles. On the other hand, mean testosterone concentration was in subject A significantly lower than in B (1,7 ± 0,06 and 3,0 ± 0,5 nmol/L, respectively). Laboratory exercise brought about a slight (less than 20%) increase in cortisol concentrations in both subjects. Those results are indicative of great between subject differences in the hormonal pattern.